Hard lessons: learning from the Charlie Gard case - Wilkinson, Dominic (Journal of medical ethics, 2018)
On 24 July 2017, the long-running, deeply tragic and emotionally fraught case of Charlie Gard reached its sad conclusion (box 1). Following further medical assessment of the infant, Charlie’s parents and doctors finally reached agreement that continuing medical treatment was not in Charlie’s best interests. Life support was subsequently withdrawn and Charlie died on 28 July 2017.Box 1 Case summary and timeline21-23Charlie Gard was born at full term, apparently healthy, in August 2016. At a few weeks of age his parents noticed early signs of muscle weakness. At 2 months of age, he was admitted to Great Ormond Street Hospital (GOSH) with poor feeding, failure to thrive and respiratory failure. He was admitted to intensive care, where investigations led to the diagnosis of a rare severe mitochondrial disorder - infantile onset encephalomyopathic mitochondrial DNA depletion syndrome (MDDS).The specific genetic form of MDDS in Charlie Gard (RRM2B) had previously been reported in approximately 15 infants, with typical clinical features including early onset, rapid progression and death in infancy.24 By that point, Charlie was paralysed and unable to breathe without respiratory support. He was found to have congenital deafness, and his heart, liver and kidneys were affected by the disorder. Doctors felt that Charlie’s prognosis was extremely poor.In early 2017, Charlie’s parents identified an experimental treatment, previously used in a different form of MDDS, which they hoped might benefit Charlie. In mouse models of a myopathic form of MDDS (TK2), early supplementation with deoxypryrimidine nucleosides apparently bypasses the genetic defect and leads to a reduction in the biochemical defect and in the severity of the clinical phenotype.25 26 Doctors at GOSH initially planned to use nucleoside treatment in Charlie, but in January he developed evidence of electrical seizures, and clinicians became convinced that treatment, both continued intensive care and the requested …